Dietary N-nitroso compounds and risk of pancreatic cancer: results from a large case–control study. (23rd November 2018) - Zheng, Jiali; Stuff, Janice; Tang, Hongwei; Hassan, Manal M; Daniel, Carrie R; Li, Donghui
Abstract: N -nitroso compounds (NOCs) are among the most potent dietary and pancreatic carcinogens. N -nitrosodiethylamine (NDEA) and N -nitrosodimethylamine (NDMA) are the most prevalent NOCs identified in foods. Using a validated and comprehensive N -nitroso database developed to estimate total NOCs and important individual NOCs from food intake, we investigated dietary exposure to NOCs in relation to pancreatic cancer in a large matched case–control study. Self-administered food frequency questionnaires were collected from 957 pathologically confirmed pancreatic ductal adenocarcinoma cases and 938 frequency-matched controls. For each food item, frequency of intake and portion size in grams was multiplied by the estimated NOC concentration from the N -nitroso database. Multiple unconditional logistic regression models were used to estimate the odds ratios (OR) and 95% confidence intervals (CIs) for pancreatic cancer risk by quartiles of NOCs and major food group contributors to NOCs, with the lowest quartile as referent. Following adjustment for confounders, we observed significant positive associations for NDEA (ORQ4 versus Q1 = 2.28, 95% CI = 1.71–3.04, P trend < 0.0001) and NDMA from plant sources (ORQ4 versus Q1 = 1.93, 95% CI = 1.42–2.61, P trend < 0.0001) with pancreatic cancer. The major food groups related to NDEA and NDMA intakes in this population were fermented cheese, pizza, grains, seafood and beer. No associations of intake of nitrate or total NOCs were observed; nitrite was inversely associated with pancreatic cancer. Although some of our findings probably reflect reverse causation bias due to lower meat intake in cases with latent disease, biologically plausible findings for pancreatic carcinogens, NDEA and NDMA, warrant further prospective investigation. Abstract : In a large scale, matched case-control study, we found significant positive associations for two potent dietary carcinogens N-nitrosodiethylamine (NDEA) and N-nitrosodimethylamine (NDMA) with risk of pancreatic cancer.